Extended 3PAKE authentication scheme for value-added services in VANETs. (April 2017) - Muthumeenakshi, R.; Reshmi, T.R.; Murugan, K.
Abstract: An authentication scheme is inevitable for providing secured communication in high-speed networks like Vehicular Ad-hoc Networks (VANETs), where node speed varies between 10 and 40 m/s. The existing authentication schemes providing value-added services in VANETs face many issues such as invalid service requests, Denial of Service (DoS) attacks, verification failures, high transmission overhead and high verification delay. To deal with the exiting issues, an Extended Three Party Password based Authenticated Key Exchange (E-3PAKE) scheme is proposed in the paper. The E-3PAKE has priority based application services that addresses the security and performance issues in existing schemes. The scheme renders a server-client authentication process and batch message dispatch to improve the efficiency of value-added services. The formal analysis done ensures the security enhancement of the scheme and the simulation results prove that the proposed scheme outperforms the existing schemes with respect to transmission overhead, verification and service response delay. Graphical abstract: